The Development of Problem-Based Culturally Responsive Learning in Enhancing Critical Thinking Skills and Cultural Literacy of Science Students - Ernawati, Tias; Dadan Rosana; Sri Atun; Susanti (Journal of Education Culture and Society, 2026)
Aim. The study aims to design and evaluate a Problem-Based Culturally Responsive Learning (PBCRL) model to improve Critical Thinking Skills (CTS) and Cultural Literacy (CL) among Indonesian students.Method. The research applied the Tjeerd Plomp development research procedure and engaged 289 Science Education students from three universities. The PBCRL model integrated problem-based learning and culturally responsive teaching into a five-stage structure. Expert validation and empirical testing confirmed the validity and reliability of both the model and its instruments. The model was initially implemented in a limited classroom setting to examine practicality and later extended to larger classes for broader testing.Results. The PBCRL model showed high practicality during initial trials. MANOVA results indicated a significant positive effect on CTS and CL, while N-Gain analysis demonstrated moderate effectiveness in improving both competencies.Conclusions. The findings confirmed that the PBCRL model is both practical and effective in enhancing CTS and CL. It provides a structured, culturally relevant framework for science education in Indonesia.Cognitive Value. This research adds value by demonstrating that integrating cultural relevance with problem-based learning strengthens students’ higher-order thinking and cultural literacy. It also delivers a validated and empirically tested instructional model that educators and researchers can adopt for multicultural classroom contexts.